Gendering Chinese religion : subject, identity, and body - Jia, Jinhua (State University of New York Press, 2014)
A gender-critical consideration of women and religion in Chinese traditions from medieval to modern times. Gendering Chinese Religion marks the emergence of a subfield on women, gender, and religion in China studies. Ranging from the medieval period to the present day, this volume departs from the conventional and often male-centered categorization of Chinese religions into Confucianism, Buddhism, Daoism, and popular religion. It makes two compelling arguments. First, Chinese women have deployed specific religious ideas and rituals to empower themselves in various social contexts. Second, gendered perceptions and representations of Chinese religions have been indispensable to the historical and contemporary construction of social and political power. The contributors use innovative ways of discovering and applying a rich variety of sources, many previously ignored by scholars. While each of the chapters in this interdisciplinary work represents a distinct perspective, together they form a coherent dialogue about the historical importance, intellectual possibilities, and methodological protocols of this new subfield.